APLIKASI METODE SIDIK CEPAT JASA LINGKUNGAN PADA DAS MIKRO (Rapid assessment method of environmental services in the micro catchment) - Anang Widicahyono; San Afri Awang; Ahmad Maryudi; Muhammad Anggri Setiawan (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2020)
ABSTRACTWatershed areas are used for a variety of environmental services that become a basic framework for watershed management activities. This study aims to develop and apply the rapid identification and assessment of environmental services at micro catchment level at Cebong Sub-watershed, Wonosobo Regency. This study uses three basic principles: (i) spatial and inter-regional relationships, (ii) causal relationship mechanism, and (iii) potential and impact values. This method is a combination of spatial analysis using Geographic Information Systems, causal relationship analysis using systems thinking, and economic valuations. The results indicated that the diversity of environmental services in the Cebong Sub-watershed are in the forms of: 1) provision services for food and water sources; 2) regulatory services for carbon stocks, and erosion and sedimentation control, 3) habitat services for iodiversity, and 4) cultural services for tourism. As food supply services, potato farming provides the highest benefit value although generate other potential environmental services. As cultural services, tourism share lower value of direct benefits, but support the sustainable use of environmental services in the watershed. This is an initiative research to develop a technical guide in managing the micro catchment based on environmental services.Keywords: rapid assesment method; environmental services; micro-catchment ABSTRAKWilayah DAS terbagi habis oleh ekosistem dengan keragaman jasa lingkungan yang dapat dijadikan sebagai kerangka dasar kegiatan pengelolaan DAS. Penelitian ini bertujuan untuk mengembangkan serta mengaplikasikan metode sidik cepat identifikasi dan penilaian jasa lingkungan pada level DAS mikro di Sub DAS Cebong, Kabupaten Wonosobo. Penelitian ini menggunakan tiga prinsip dasar: (i) spasial dan hubungan antar wilayah, (ii) mekanisme hubungan sebab akibat, serta (iii) nilai potensi dan dampak. Metode sidik cepat jasa lingkungan merupakan kombinasi analisis spasial dengan pemanfaatan Sistem Informasi Geografis, analisis hubungan sebab akibat dengan metode system thinking, serta valuasi ekonomi. Hasil identifikasi sidik cepat menunjukkan keragaman jasa lingkungan di Sub DAS Cebong berupa: 1) jasa penyediaan dengan jasa utama sumber makanan dan air domestik, 2) jasa regulasi dengan jasa utama cadangan karbon dan pengendalian erosi sedimentasi, 3) jasa habitat dengan jasa utama biodiversitas, dan 4) jasa budaya dengan jasa utama pariwisata. Jasa penyediaan makanan dalam bentuk pertanian kentang memberikan nilai manfaat paling tinggi, namun memunculkan penurunan potensi jasa lingkungan lainnya. Jasa budaya berupa pariwisata, meskipun nilai manfaat langsungnya lebih rendah, namun dapat mendukung keberlanjutan pemanfaatan jasa lingkungan di dalam DAS. Penelitian ini menjadi sebuah inisiasi petunjuk teknis rencana pengelolaan DAS mikro berbasis jasa lingkungan.Kata kunci: metode sidik cepat; jasa lingkungan; DAS Mikro